Effects of emotional intelligence on leadership effectiveness: A comparative analysis between Malaysian and Japanese business leaders - Aahad, M. Osman-Gani; Kobayashi, Kiyoshi; Kabir, Sardar Md Humayun (2019)
Organizations are now experiencing shortage of effective leaders resulting in slower growth rates of corporate performance. Leadership effectiveness is very crucial for organizational success and growth. A leader, who is emotionally intelligent, can manage own emotions and understand others’ emotions thereby can influence subordinates’ performance. Visionary leaders with high emotional intelligence were found to facilitate implementing major organizational change in their organizations. Previous researchers have emphasized the need and significance of emotional intelligence for leadership effectiveness, but very few have compared the impacts of such competency among leaders from different national backgrounds. This paper empirically investigated the effects of emotional intelligence on leadership effectiveness in Japan and Malaysia. Primary data was collected from 186 business managers as well as from their subordinates working in different corporate offices operating in Peninsular Malaysia and Japan. Structural equation modeling technique was applied for conducting data analyses and the results showed that Malaysian managers’ emotional intelligence had more significant positive effects on leadership effectiveness than Japanese managers. The empirical evidence from the findings of this study will contribute to developing new knowledge in the theoretical domains of leadership, management and organizational behavior. The findings will also help in making new organizational policy decisions on developing Leadership competencies for enhancing emotional intelligence, as well as for developing new professional competencies of modern leaders. Implications for future research and professional practice are discussed at the end of this paper.